Anaerobic digestion of saline waste activated sludge and recovering raw sulfated polysaccharides. (September 2021) - Liu, Jie; Zhang, Zi; Xue, Weiqi; Siriweera, Withanage B.; Chen, Guanghao; Wu, Di
Graphical abstract: Highlights: Examining the possibility of recovering sulfated polysaccharides (SPs). Over 50% of SPs could be recovered from anaerobic digested sludge. All extracted SPs samples were in high purity > 80% of the total mass. Total metal in SPs samples only accounted for < 2% of the total mass. All extracted SPs samples appeared certain bioactivities. Abstract: This study investigated a new bioresource technology of recovering raw chemicals of sulfated polysaccharides (SPs) from the digested saline waste activated sludge (WASsaline ) that naturally contained 3–30% (w/w) of SPs. Two bench-scale anaerobic digestion (AD) experiments were conducted under mesophilic and thermophilic conditions; the effectiveness of extracting SPs from digested WASsaline and the biochemical characteristics of SPs were examined. After 20-days of digestion, the results showed that approximately 54 – 58% of initial total SPs in WASsaline were recoverable, in which 38 – 48% in solid digestate and 10–15% in liquid supernatant). The extracted raw chemicals of SPs were proven to be of high purity (>80%) and demonstrating significant properties such as anti-inflammation, anti-oxidation, and anti-coagulation for potential pharmaceutical-like application.